Progress of Geodesy Related Ionosphere from Chinese Scientists in the Period of 2019—2023 - Zishen LI, Ningbo WANG, Ang LIU, Ang LI, Heng YANG, Dongshen ZHAO, Xiaodong REN, Andong HU (Journal of Geodesy and Geoinformation Science, 2023)
The ionosphere is the ionized part of the upper atmosphere of the Earth, which plays an important role in atmospheric electricity and forms the inner edge of the magnetosphere. It influences radio propagation significantly, such as the Global Navigation Satellite System (GNSS). Meanwhile, the GNSS is also an essential technique for sensing the variation of ionosphere. During the years of 2019—2023, a large number of Chinese geodesy scientists devoted much efforts to the geodesy related ionosphere. Due to the very limited length, the achievements are carried out from the following six aspects, including: ① The ionospheric correction models for BDS and BDSBAS; ② Real-time global ionospheric monitoring and modeling; ③ The ionospheric 2D and 3D modeling based on GNSS and LEO satellites; ④ The ionospheric prediction based on artificial intelligence; ⑤ The monitoring and mitigation of ionospheric disturbances for GNSS users; ⑥ The ionospheric related data products and classical applications.